The Hungarian surgeon Dr. Haraszti with the political commissionar and the commander of the Rákosi-Battalion near Madrid. Place of persons on back. Series of 2 photos. Copied from collection Museum für Deutsche Geschichte (1937)
The Hungarian surgeon Dr. Haraszti with the political commissionar and the commander of the Rákosi-Battalion near Madrid. Place of persons on back. Series of 2 photos. Copied from collection Museum für Deutsche Geschichte.